Non-native Nematode Ashworthius sidemi Currently Dominates the Abomasal Parasite Community of Cervid Hosts in the Czech Republic - Magdálek, Jan; Bourgoin, Gilles; Vadlejch, Jaroslav (Frontiers in Veterinary Science, 2022)
Ashworthius sidemi is a non-native abomasal nematode introduced in Europe via sika deer in the late 19th and early 20th centuries. The current dynamic spread of this parasite amongst autochthonous wild cervids occurs independently of human activities, and A. sidemi may pose a threat to the conservation of endangered wild ungulates and to livestock. This invasive parasite has been previously detected in the Czech Republic, but more accurate information on A. sidemi is required. Only limited information is generally available on the factors influencing the spread of abomasal nematodes in wild ruminants, so more information is necessary for planning effective strategies of parasite control. We therefore conducted a survey on the abomasal nematodes in cervids in both game reserves and hunting grounds across the Czech Republic, taking into account the hosts and environmental factors. The abomasa of 104 animals belonging to five cervid species originating from various locations of the country were collected. Data on host (species, sex, and age group) and the monthly average temperature in the region were obtained for each animal. The parasitological analyses indicated that 92% of the abomasa were infected by nematodes. A. sidemi was the most prevalent (72%) and abundant (80% of the total recovered individuals) nematode species and was detected in all cervid species except white-tailed deer. The abundance of A. sidemi was highest in roe deer and fallow deer, but A. sidemi abundance did not depend substantially on the host or environmental factors. In contrast, the abundance of nematodes from the subfamily Ostertagiinae was influenced by the host species and temperature. Parasitic load was significantly higher in roe deer and during the warmer periods of the survey. We also detected another non-native nematode species, Spiculopteragia houdemeri. Our study provides an overview of the communities of abomasal nematodes parasitising cervid hosts in the Czech Republic that indicate the superiority of a non-native nematode, A. sidemi. Our results outline some important factors affecting the spread of abomasal nematodes under the current conditions in the Czech Republic.